2004
DOI: 10.1194/jlr.m300392-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Presence of unsaturated sphingomyelins and changes in their composition during the life cycle of the moth Manduca sexta

Abstract: NMR and electrospray ionization tandem mass spectrometry were used to show for the first time the presence of sphingomyelins in extracts of the tobacco hornworm Manduca sexta ( Lepidoptera ). The sphingosine in the ceramide was identified as tetradecasphing-4-enine, and the fatty acids were C18:0, C20:0, C22:0, and C24:0 (compound 1). Heterogeneity in the ceramide was observed in sphingomyelins from M. sexta. All of the sphingomyelins were associated with their doubly unsaturated sphingosine, tetradecasphing-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…S5 in the supplementary material). Lipids with a similar sphingadiene LCB have been described in Drosophila (Fyrst et al, 2008) and Manduca (Abeytunga et al, 2004). Interestingly, a significant proportion of these sphingolipids contained N-amide-bound fatty acids that were a-hydroxylated (Fig.…”
Section: Sterol Depletion Alters Abundance Of Specific Sphingolipid Vmentioning
confidence: 92%
“…S5 in the supplementary material). Lipids with a similar sphingadiene LCB have been described in Drosophila (Fyrst et al, 2008) and Manduca (Abeytunga et al, 2004). Interestingly, a significant proportion of these sphingolipids contained N-amide-bound fatty acids that were a-hydroxylated (Fig.…”
Section: Sterol Depletion Alters Abundance Of Specific Sphingolipid Vmentioning
confidence: 92%
“…we identified a family of endogenous sphingolipids containing a D 4,6 -sphingadiene LCB. Although not studied extensively, D 4,6 -sphingadienes have been reported in insect species, indicating that these structures may be conserved among dipteran insects (19,20). In contrast, sphingadiene LCBs, with the double bonds at C4 and C8, have been identified in numerous species.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the D 4,6 -sphingadiene-containing ceramides were found to have potent although diverse biological effects. The ceramide compound from M. sexta was found to increase apoptosis in an embryonic M. sexta cell line (19), whereas the compound from B. mori was shown to promote neurite outgrowth in the rat pheochromocytoma cell line PC12 (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct recognition of sphingosines by N. rileyi conidia requires the expression of sphingosine receptors on the surface components of conidia (the rodlet layer 18) ), so sphingosine receptors may belong to a new type of receptor family. Almost all sphingoid bases from insects (Drosophila melanogaster, 19) Drosophila sphingadienes, 20) and Manduca sexta 21) ), which are not known as hosts of N. rileyi, carry 14 carbon atoms in the structure of the sphingoid base. Since 18 and 20 carbon atoms of the sphingoid base are commonly found in mammalian 22,23) and yeast cells, [24][25][26] 14 carbon atoms of the sphingoid base appear to be insect-specific.…”
Section: Resultsmentioning
confidence: 99%